MODEL SPASIAL EKOLOGIS PRODUKTIVITAS PRIMER EKOSISTEM PERAIRAN PANTAI DELTA MAHAKAM DENGAN TEKNIK PENGINDERAAN JAUH - , Umi Zakiyah, Ir.,M.Si.; , Prof. Dr. Hartono, DEA DESS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research has been done in Delta Mahakam ecosystem in April 2008. The aims were to observe, analyze and evaluate the abiotic, biotic and socio- cultural variables, their effect and relations with primary productivity and implemented âcase two waterâ primary productivity based developed model for this area of interest. Primary productivity model used is case 2 waters Photosynthetic Available Radiation based Primary Productivity model developed by Asanuma (2002) and further developed by submitting Total Suspended Matter (TSM) as new variable. Data used are includes TERRA and AQUA remotely sensed data and in situ data for validation purposes. Satellites data were processed using ENVI and ER MAPPER software and interpreted as well as analyzed using SeaDAS and IDL. The correlation between the in situ data and the derived satellites data with primary productivity, also between the in situ primary productivity to the model based primary productivity were analysed by Multiple Regression Analysis using SPSS 16.0. The results showed that all water quality variables values are within optimal range except TSM as it tends to increase. The socio-cultural observation showed an increase of conflicts in the society and mostly closely related to the increase of interest in resources utilizations. All observed variables has affected the condition of primary productivity which relatively low in status (mesothrophic). The correlation between the in situ based and model based primary productivity showed coefficient correlation of 70 percents, while all variables effect the primary productivity significantly. The model has proven that the Delta Mahakam ecosystem ecospatially has degraded in its quality. Thus, it is suggested that the local Government still in need to slower the environmental degradation processes for longer sustainability of the resources in Delta Mahakam coastal area.